OPTIMALISASI PELAYANAN BINA KOMUNIKASI MELALUI PROGRAM PERSEPSI BUNYI DAN IRAMA (BKPBI), UNTUK ANAK YANG BERKEBUTUHAN KUSUS TUNARUNGGU DI SDLB NEGERI JENANGAN PONOROGO - Suhartini, Endang; Murdianto, Murdianto; Setyowati, Nanik (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2021)
Children with special needs are children with different characteristics from normal children in general. Especially deaf children are children who have impaired hearing either totally or have residual hearing. Deaf communication requires services that can support their communication difficulties. In this case SDLB Negeri Jenang Ponorogo organized a communication development program with Communication Development through the Sound and Rhythm Perception Program (BKPBI). In this study the author is intended to discuss more about; Forms of service stages, learning implementation strategies and service results of sound and rhythm perception programs in SDLB Negeri Jenang Ponorogo. This research uses a qualitative approach methodology with the type of case study research. The data in this study are words and actions, while the source of the data are the Principal and teachers at SDLB Negeri Jenang. Data collection methods are interviews, observation, and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. After conducting the analysis, the writer can conclude that the form of communication service development stages through sound and rhythm perception programs in the Jenang Negeri Extraordinary Elementary School is sound detection, sound discrimination, sound identification, sound comprehension, learning implementation strategies using review, overview, presentation, exercise, and summary, also by using the classical and individual models, while the results of the service program of perception of sound and rhythm in the State Elementary School Extraordinary, namely deaf children are able to recognize sounds, easy to respond to sounds such as background noises, the nature of sounds, creating sounds up to recognize types of musical instruments, able to identify sounds and detect the direction of sound.